2017
DOI: 10.1063/1.4979173
|View full text |Cite
|
Sign up to set email alerts
|

High performance 3D printed electronics using electroless plated copper

Abstract: This paper presents design and performance validation of 3D printed electronic components, 3D toroidal air-core inductors, fabricated by multi-material based Fused Deposition Modelling (FDM) 3D printing technology and electroless copper plating. Designs of toroidal inductor is investigated with different core shapes and winding numbers; circular and half-circular cores with 10 and 13 turns of windings. Electroless plated copper thin film ensures 3D printed toroidal plastic structures to possess inductive behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 14 publications
0
21
0
Order By: Relevance
“…Reproduced under the terms of the CC-BY 4.0 license. [78] Copyright 2017, The Authors, published by AIP Publishing. f) 3D printed metal electrodes coated with Au and Bi for heavy metal detection (scale bar: 1 cm).…”
Section: Extrusion-based 3d Printingmentioning
confidence: 99%
See 1 more Smart Citation
“…Reproduced under the terms of the CC-BY 4.0 license. [78] Copyright 2017, The Authors, published by AIP Publishing. f) 3D printed metal electrodes coated with Au and Bi for heavy metal detection (scale bar: 1 cm).…”
Section: Extrusion-based 3d Printingmentioning
confidence: 99%
“…Various studies have been extensively reported to fabricate Cu conducting paths using a chemical deposition. [76][77][78] Cu thin films have been patterned on substrates by electroless deposition (ELD) technique at low temperature. ELD, as one of the chemical deposition methods, is an alternative approach to obtain the structures coated with conducting materials and offers a low temperature and costeffective method for metal deposition on insulating substrates.…”
Section: Chemical Deposition For 3d Structural Devicesmentioning
confidence: 99%
“…Alternative strategies for the fabrication of traces or interconnects on nonplanar surfaces based on direct write printing of metallic inks or composites, inkjet printing, metalizing objects fabricated via fused deposition modeling, hydroprinting of silver nanoparticles, pop‐up assemblies created using prestrained elastomeric substrates, and networks of liquid metal wires, and patterning via controlled flocculation in microchannels, have been reported. These approaches, however, require specialized instruments (e.g., 3D printers with multiaxial movement) and they are limited to certain types of target materials.…”
Section: Introductionmentioning
confidence: 99%
“…Electroless plating is a popular and mature technique to create metallic coating on plastic objects, including 3D printed plastic parts. 26,27 However, although electroless plating is a commonly-used approach to achieve conformal metal coating on plastic surfaces, challenge remains to achieve selective coating on specic locations. Trace metal particle residues can still form on substrate and results in shorted electrical circuits or the low-performance of 3D metal structures.…”
Section: Introductionmentioning
confidence: 99%